Strategi public relation pemerintah dalam sosialisasi literasi keuangan syariah kepada masyarakat - wardani, yuke ivana kusuma (Maliki Interdisciplinary Journal, 2025)
Indonesian abstract. Increasing understanding of Islamic finance is a very important agenda for the Indonesian government in strengthening the Islamic economic ecosystem in the country. However, the low public knowledge about the concept of Islamic finance remains a major challenge. In this regard, the role of government Public Relations (PR) is crucial in disseminating information and building public trust through effective communication. This study aims to analyze the government's PR approach in disseminating Islamic financial literacy to the public based on a literature review of journals and official documents. The study findings indicate that the government's PR strategy includes strengthening public communication by utilizing digital media, inter-agency collaboration, tailoring educational messages for various segments, and continuous evaluation to assess the success of the program. An approach designed in a participatory manner and based on Sharia values can enhance public understanding and participation in Sharia financial services